APPLICATION OF CONSTRUCTIVE PLAYING METHODS TO IMPROVE SOCIAL AND COGNITIVE SKILLS (Study on PAUD Al Wakhidah Village Pasar Bembah, Air Napal District, North Bengkulu Regency) - Nurlena Nurlena; Nina Kurniah (DIADIK, 2018)
The purpose of this study is to describe the application of constructive playing methods in improving children's social and cognitive skills in Al Wakhidah ECD Village Pasar Bembah Village, Air Napal District, North Bengkulu. The research method used is Class Action Research. The subjects of this study were 15 students from class B1 consisting of 7 girls and 8 boys. The technique of collecting data uses an observation / observation sheet. This research was conducted in three cycles. The results of the study stated that it turned out that children's social skills increased between cycles 1, with an average of 2.23 in the second cycle increasing to 2.86 and increasing also in the third cycle to 3.68. While children's cognitive abilities increase between cycles 1 with an average of 2.23 to 3.15 in cycle 2 and increase also in cycle 3 to 3.76. So that it has been proven that the application of constructive play methods can improve children's social and cognitive skills in Al Wakhidah ECD Village Pasar Bembah, Air Napal District, North Bengkulu